2016
DOI: 10.1016/j.ajog.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal survival after endoscopic equatorial laser for the treatment of twin-to-twin transfusion syndrome

Abstract: Endoscopic equatorial laser therapy was associated with a survival of both and at least 1 twin of approximately 55% and 83%, respectively, with a low rate of recurrent twin-to-twin transfusion syndrome and twin anemia-polycythemia sequence. In addition, the preoperative finding of abnormal donor umbilical artery Doppler on ultrasound identified a subgroup of twin-to-twin transfusion syndrome pregnancies with a lower dual survival rate caused by increased intrauterine deaths of donor twins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
4
15
3
Order By: Relevance
“…Two hundred and thirty studies were therefore deemed eligible after full‐text review. From these, all randomized trials ( n = 6) and the largest observational studies ( n = 94) were selected for analysis (Figure ). There were 13 case–control studies, 32 prospective cohort studies and 49 retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Two hundred and thirty studies were therefore deemed eligible after full‐text review. From these, all randomized trials ( n = 6) and the largest observational studies ( n = 94) were selected for analysis (Figure ). There were 13 case–control studies, 32 prospective cohort studies and 49 retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…A 400‐μm diameter diode laser fiber (Dornier Med Tech, Wessling, Germany) with a power output of 20 to 30 W was used for coagulation of the placental surface. All visible intertwin vascular anastomoses were coagulated with additional laser ablation of the placental tissue between the coagulated vessels, as previously described . Subsequently, amnioreduction of the polyhydramnios was undertaken through the cannula over a period of 10 to 15 minutes to obtain subjective normalization of the amniotic fluid volume on ultrasound.…”
Section: Methodsmentioning
confidence: 99%
“…Fichera et al 21 reported four miscarriages, six cases of pre-term birth, 7 NICU admissions and one neonatal death in their ten cases of TTTS diagnosed before 18 weeks gestation. 23 Other outcomes which were reported in case reports included intra-twin arteriovenous fistula of the placenta, 24 a pseudoamniotic band syndrome, 25 acute reversal of oligohydramniospolyhydramnios sequence 16 and the difficulty in managing presumed TTTS in a twin pregnancy presenting with lambda sign. Rates of all these complications were lower in the patients who underwent fetoscopy >18 weeks.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Persico et al reported one case of PPROM <24 weeks leading to miscarriage and one neonatal death in the 29 patients who were diagnosed with TTTS before 18 weeks gestation. 23 Other outcomes which were reported in case reports included intra-twin arteriovenous fistula of the placenta, 24 a pseudoamniotic band syndrome, 25 acute reversal of oligohydramniospolyhydramnios sequence 16 and the difficulty in managing presumed TTTS in a twin pregnancy presenting with lambda sign. 20 Outcomes which were reported in the case series' included three cases of intestinal complications following laser treatment of TTTS, two of which were diagnosed with TTTS before 18 weeks (one intestinal atresia and one necrotising enterocolitis), 26 and another paper looking at the incidence of pseudoamniotic band syndrome following laser to treat TTTS in which two of the eight cases were diagnosed and had surgery before 18 weeks gestation.…”
Section: Systematic Reviewmentioning
confidence: 99%